2022
DOI: 10.1017/qua.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Environmental changes in SW France during the Middle to Upper Paleolithic transition from the pollen analysis of an eastern North Atlantic deep-sea core

Abstract: Evaluating synchronies between climate and cultural changes is a prerequisite for addressing the possible effect of environmental changes on human populations. Searching for synchronies during the Middle-Upper Paleolithic transition (ca. 48–36 ka) is hampered by the limits of radiocarbon dating techniques and the large chronological uncertainties affecting the archaeological and paleoclimatic records, as well by their low temporal resolution. Here, we present a high-resolution, pollen-based vegetation record f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 131 publications
1
7
0
Order By: Relevance
“…The glacier front at Lake Enol and Vega de Comeya reached its maximum extension from 44 to 38 ka Jim enez-S anchez et al, 2013), when colder and drier conditions in the mountain areas dramatically affected the tree cover. Consistently, pollen data from the marine core MD04-2845 in the Cantabria Sea (S anchez Goñi et al, 2008) show a low abundance of arboreal pollen with a saw-teeth pattern between 50 and 40 ka BP, suggesting a long-term forest opening from GI2 to GI8 in Atlantic forests (Fourcade et al, 2022). From ca.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The glacier front at Lake Enol and Vega de Comeya reached its maximum extension from 44 to 38 ka Jim enez-S anchez et al, 2013), when colder and drier conditions in the mountain areas dramatically affected the tree cover. Consistently, pollen data from the marine core MD04-2845 in the Cantabria Sea (S anchez Goñi et al, 2008) show a low abundance of arboreal pollen with a saw-teeth pattern between 50 and 40 ka BP, suggesting a long-term forest opening from GI2 to GI8 in Atlantic forests (Fourcade et al, 2022). From ca.…”
Section: Discussionsupporting
confidence: 54%
“…A highly variable climatic response is shown in the Cantabrian region during the Middle to Upper Palaeolithic transition. This variability is most likely linked to the abrupt shifts expected from the alternating stadial and interstadial episodes within each phase during the MIS 3, as has been recorded in the marine core in Biscay Bay (Fourcade et al, 2022;S anchez Goñi et al, 2008). It was observed that both stadial and interstadial alternating phases occurred during the Mousterian, Aurignacian and Gravettian levels; showing that both Neanderthals and AMH were subsisting during both cold and temperate events in northern Iberia.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This may impact the length of overlap between Neanderthal and anatomically modern humans in Eurasia . Therefore, we used the archaeological synthesis based on the most recent 14 C calibration curve IntCal20 (Brad et al, 2020; Djakovic et al, 2022;Fourcade et al, 2022;Rios-Garaizar et al, 2022;Guérin et al, 2023). We also remodel the Châtelperronian time-range from the Ormesson site, using the ages of Bodu et al (2017), with the same method as Fourcade et al (2022).…”
Section: Archeological Dating Modelmentioning
confidence: 99%
“…Several hypotheses have been invoked to explain the Neanderthals disappearance. Recent updated archaeological synthesis shows that the onset of the Homo sapiens occupation of western Europe likely preceded the extinction of Neandertals (Talamo et al, 2020;Fourcade et al, 2022;Rios-Garaizar et al, 2022;Djakovic et al, 2022). This overlap may have led to competitive exclusion (Banks et al, 2008), assimilation (Smith et al, 2005) or demographic weakness (Degioanni et al, 2019).…”
Section: Introductionmentioning
confidence: 99%